TEACHING AND LEARNING GRAMMAR AND STYLE IN WRITING - A PRACTICAL APPROACH - Larcy C Abello (Soegijapranata Catholic University, 2015)
This report focuses on the exploration of the three dimensions of grammarform, meaning, and usea practical approach to teach and learn grammar and style and effect communication. Using journalistic, literary, and academic/scientific/technical texts, this describes the teaching-learning process involved in language activities, such as text analysis, text conversion, and writing